1998
DOI: 10.1104/pp.116.1.369
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Stereospecificity of the First Three Enzymes of 3-Dimethylsulfoniopropionate Biosynthesis in a Chlorophyte Alga1

Abstract: Many marine algae produce 3-dimethylsulfoniopropionate (DMSP), a potent osmoprotective compound whose degradation product dimethylsulfide plays a central role in the biogeochemical S cycle. Algae are known to synthesize DMSP via the four-step pathway, L-Met 3 4-methylthio-2-oxobutyrate 3 4-methylthio-2-hydroxybutyrate 3 4-dimethylsulfonio-2-hydroxy-butyrate (DM-SHB) 3 DMSP. Substrate-specific enzymes catalyzing the first three steps in this pathway were detected and partially characterized in cell-free extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
62
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 37 publications
2
62
0
Order By: Relevance
“…Microalgae, such as sea-ice diatoms, are believed to utilize an alternative Met transaminase pathway. Radiolabeling studies of pathway metabolites showed algal DMSP synthesis sequentially utilizes 2-oxoglutarate-dependent aminotransferase, NADPH-linked reductase, S-adenosyl Met (SAM)-dependent methyltransferase (SAMmt), and oxidative decarboxylase (Gage et al, 1997;Summers et al, 1998). Analyzed most extensively in the green macroalgae, Ulva intestinalis, radiolabeled metabolites also supports presence of this pathway in haptophyte, diatom, and prasinophyte species.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Microalgae, such as sea-ice diatoms, are believed to utilize an alternative Met transaminase pathway. Radiolabeling studies of pathway metabolites showed algal DMSP synthesis sequentially utilizes 2-oxoglutarate-dependent aminotransferase, NADPH-linked reductase, S-adenosyl Met (SAM)-dependent methyltransferase (SAMmt), and oxidative decarboxylase (Gage et al, 1997;Summers et al, 1998). Analyzed most extensively in the green macroalgae, Ulva intestinalis, radiolabeled metabolites also supports presence of this pathway in haptophyte, diatom, and prasinophyte species.…”
mentioning
confidence: 99%
“…conversion of Met to DMSP based on radiolabeling metabolite studies (Gage et al, 1997;Summers et al, 1998) would be elevated in association with salinityinduced DMSP elevation. Eighteen of the 36 proteins increased under high-salinity/DMSP conditions classified within the four enzyme classes in the proposed Met-DMSP synthesis pathway (Fig.…”
Section: Candidate Dmsp Synthesis Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…The sulfate is subsequently transported into the chloroplasts, where it is reduced to sulfide in the presence of glutathionine and then transformed into cysteine. Cysteine is used to synthesize methionine, which is then transformed into DMSP via one of three pathways that differ among taxonomic groups of plants and algae (9)(10)(11)(12). Thus, the biosynthesis of DMSP ultimately depends on the activity of the sulfate assimilation pathway; however, little is known about how DMSP synthesis differs among algae from diverse origins, except that the whole molecule is derived from sulfur amino acids.…”
mentioning
confidence: 99%